1978
DOI: 10.1002/ijc.2910220102
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressing breast cancer (poussée Évolutive) in Tunisia: Studies on delayed hypersensitivity

Abstract: Delayed hypersensitivity reactions to a battery of antigens were measured in 145 Tunisian breast cancer patients to determine whether an immunologic mechanism could be detected which might explain the high frequency (60%) of the rapidly progressing form in Tunisian breast cancer patients. Although a greater proportion (30%) of patients with rapily progressing breast cancer reacted to extracts of a breast tumor antigen (2937) than patients without PEV (9%), no significnat difference between PEV and non-PEV pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Fifth, the finding that inflammatory breast cancer patients in Tunis reacted to soluble breast cancer antigen with a frequency three times greater than the reaction in other types of breast cancer patients was unexpected and quite contrary to what was anticipated [22]. This study complements the findings of Stewart and Orizaga [25] and suggested an augmented host reactivity in this subset of breast tumors that have the worst prognosis.…”
Section: Paradoxical or Anomalous Observationssupporting
confidence: 47%
See 2 more Smart Citations
“…Fifth, the finding that inflammatory breast cancer patients in Tunis reacted to soluble breast cancer antigen with a frequency three times greater than the reaction in other types of breast cancer patients was unexpected and quite contrary to what was anticipated [22]. This study complements the findings of Stewart and Orizaga [25] and suggested an augmented host reactivity in this subset of breast tumors that have the worst prognosis.…”
Section: Paradoxical or Anomalous Observationssupporting
confidence: 47%
“…No correlation Griffith et al [12] 77 3 Elston et al [13] 1562 10 Bad prognosis Leitch [14] 5 Months Schumann [15] 11 Months Learmonth [16] 46 5 Lee and Tannenbaum [17] 28 5 Pfahler and Case [18] 15 5 Taylor and Meltzer [19] 38 2 Droulias et al [20] 75 18 Lucas and Perez-Mesa [21] 58 5 Mourali et al [22] 145 NA Levine et al [23] 134 (42) NA Costa et al [24] 94 NA Stewart and Orizaga [25] 56 5 Champion et al [26] 496 6 Morrison et al [27] 253 3 Fisher et al [28] 62 NA Flores et al [29] 95 10 Meyer and Hixon [30] 133 5 Fisher et al [31] 522 5 Fisher et al [32] 522 5 Parkes et al [33] 34 11 Rosen and Groshen [34] 644 18 van Netten et al [35] 25 NA Pupa et al [36] 1200 19…”
Section: Authormentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed hypersensitivity studies using microbial antigens and in vitro studies including lymphocyte transformation tests and measurements of B and T cells indicated that cases with rapid progression and IBC-like symptoms had an immune response comparable to that of other breast cancer patients, suggesting that rapidly progressing breast cancer is not a reflection of immunodeficiency [59]. In fact, a greater reaction to breast-tumorrelated antigens was elicited in breast cancer patients with IBC-like symptoms than in other breast cancer patients [67], suggesting a hyperimmune response in those with rapidly progressing breast cancer. It is notable that other evidence also suggests that the immune response may facilitate breast cancer development.…”
Section: Immunologic Factorsmentioning
confidence: 89%
“…The etiology of IBC has been examined in one case-case study of 68 IBC cases in the United States [24] and one case-case study in Pakistan [12]. The etiology of rapidly progressing breast cancer, which encompasses IBC as well as milder forms of the disease, has also been studied in case-comparison studies conducted in Tunisia in the 1970s and 1980s [58,59,67,68,83]. Information on associated factors is also available from case series.…”
Section: Analytic Datamentioning
confidence: 99%